Les guerres de religion - Miquel, Pierre, 1920-2003 (Paris : Fayard, 1980)
Trois siècles de violences - La haine et la peur - La rage de tuer - L'exil et la résistance
Keywords: Catholic Church -- History -- France; Protestants -- History -- France; religious wars; index; bibliography; France -- History -- 16th century; France -- History -- Bourbons, 1589-1789.; France -- Church history